Psychological stressor caused alpha-male non-human-primate Macaca fascicularis to become agonistic when struggling over food - Rosyid Ridlo Al Hakim; Erie Kolya Nasution (Utan Kayu Publishing, 2021)
Primates are the object of increased research recently. Experiments on non-human-primates (NHP) can determine their psychological level. NHP Macaca fascicularis is a primate that lives socially with a social hierarchy. Alpha-male becomes the leader of the group. Beneficial access is higher in alpha-male, against the conflicts to be initiated for certain interests. This study provides an overview of alpha-male aggressiveness in groups based on psychological stressors obtained during field observations. The research was conducted at Mbah Agung Karangbanar Religious Tourism Park, Central Java, Indonesia, group-size of 12 adult male, 14 adult female, 8 sub-adult male, 9 sub-adult female, 10 juvenile male, 14 juvenile female, and 6 infants. Aggressive observation (sampling-rules) is behavioral-animal sampling on alpha-male individuals and one individual for each age group as the subject of observation. Observations were carried out for 8 days with one-zero sampling. Adult male and alpha-male aggressive behavior ranked the highest during observation, that psychological stressors obtained.